In search of the Mexican Beverly Hills : Latino suburbanization in postwar Los Angeles - Gonzalez, Jerry, 1978- (Latinidad., 2018)
"Residential and industrial sprawl changed more than the political landscape of postwar Los Angeles. It expanded the employment and living opportunities for millions of Angelinos into new suburbs. In Search of the Mexican Beverly Hills examines the struggle for inclusion into this exclusive world--a multilayered process by which Mexican Americans moved out of the barrios and emerged as a majority population in the San Gabriel Valley--and the impact that movement had on collective racial and class identity. Contrary to the assimilation processes experienced by most Euro-Americans, Mexican Americans did not graduate to whiteness on the basis of their suburban residence. Rather, In Search of the Mexican Beverly Hills illuminates how Mexican American racial and class identity were both reinforced by and took on added metropolitan and transnational dimensions in the city during the second half of the twentieth century"--